Amorphous zirconium oxide activates peroxymonosulfate for selective degradation of organic compounds: Performance, mechanisms and structure-activity relationship. (1st January 2023) - Li, Xiaoyang; Lv, Ruolin; Zhang, Weiming; Li, Mingyang; Lu, Junhe; Ren, Yi; Yin, Yue; Liu, Jiahang
Highlights: ZrO2 with non-redox properties enabled highly-efficient peroxymonosulfate activation. The activity of ZrO2 was 5.1–72.0 times higher than conventional redox-metal oxides. The surface complexes were identified as the principal reactive species. The density of surface hydroxyl groups governed the formation of surface complexes. Abstract: Application of heterogeneous advanced oxidation processes (AOPs) for wastewater treatment suffers from the low oxidant utilization efficiency, slow catalytic cycling and severe matrix interference. Herein, we report that amorphous zirconium dioxide (aZrO2 ), a redox-inert metal oxide, can efficiently activate peroxymonosulfate (PMS) to degrade organic micropollutants under very low oxidant doses and complex coexisting matrices. Distinct from conventional AOPs where radicals are formed, the surface Zr(IV)-PMS* complex was identified as the principal reactive species, and primarily conducted oxygen-atom-transfer route with selected molecules. Quantitative structure-activity relationship analysis indicated that the formation of Zr(IV)-PMS* complex was governed by the density of the surface hydroxyl groups. The strong interaction between the Zr atom and PMS caused the deviation of the negative charge from Zr(IV) metal sites to the oxidant. As a result, the O-O bond of the adsorbed PMS was prolonged and its oxidation potential elevated, which enabled it to directly react with contaminants. This study indicates the potential of aZrO2 as a novel and eco-friendly catalyst that activates PMS to selectively tackle organic contaminants, and sheds light on the designing of Fenton-like catalysts using redox-inert metals. Graphical abstract: Image, graphical abstract A novel redox-inert metal oxide, amorphous zirconium dioxide (aZrO2 ), is surprisingly capable of highly efficient decontamination through peroxymonosulfate (PMS) activation. The activity of aZrO2 in CBZ degradation is 5.1 to 72.0 times higher than the conventional transition metal oxides. The surface Zr(IV)-PMS* complex was identified as the principal reactive species, and primarily conducted oxygen-atom-transfer route with selected molecules. Quantitative structure-activity relationship analysis indicated that the formation of surface complex was governed by the density of the surface hydroxyl groups on the aZrO2 particles.